Rekonstruksi Otoritas Keilmuan dalam Pendidikan Islam di Era Kecerdasan Buatan: Analisis Sosiologis atas Pergeseran Relasi Guru dan Pengetahuan - Sabariah Sabariah; Indah Syahputri; Affryyana Febbryyana. L; Sheilla Salsabilla; Nurindah Hasanah; Agi Ashari; Sultan Halipah (Yayasan Albahriah Jamiah Indonesia, 2026)
The transformation of the use of artificial intelligence (AI) in education has changed patterns of access, production, and distribution of knowledge, including in Islamic education. The increasing dependence of students on AI systems as a source of religious information raises questions about epistemic legitimacy, shifts in scientific authority, and the relevance of knowledge transmission models that have traditionally relied on teacher-student relationships. Although studies on the digitalization of Islamic education continue to develop, analysis of the reconstruction of scientific authority in the context of the interaction between normative and algorithmic authority remains relatively limited. This study aims to analyze the shifting relationship between teachers and knowledge and to formulate a model for reconstructing scientific authority in Islamic education in the AI era. The study uses a qualitative approach, grounded in a literature review and employing critical content analysis, to examine the sociology of education, scientific authority, Islamic epistemology, and the development of AI. The results show that AI encourages the deconstruction of scientific authority from a centralized model to a distributed epistemic network, enabling more open, cross-authority access to knowledge. In this context, teachers no longer function as the sole source of knowledge but have transformed into epistemic mediators, information curators, truth validators, and digital literacy facilitators. Research also finds that the legitimacy of knowledge has shifted from the dominance of sanad (traditional chain of transmission) and personal authority to a hybrid mechanism that combines scientific credibility, digital verification, information accuracy, and algorithmic transparency. These findings produce a hybrid-collaborative model of scientific authority that emphasizes that contemporary Islamic educational authority is constructed through negotiations between scientific competence, epistemic ethics, and digital curation capacity, thus enriching the study of the sociology of Islamic education in the face of technological disruption.